1999
DOI: 10.1007/s11745-999-332-5
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal serum lysophospholipids in multiple myeloma patients

Abstract: Lysophosphatidylcholine (LPC) and lysophosphatidic acid (LPA) mediate various kinds of biological activities and play an important role in cellular signal transduction. We analyzed serum phospholipids obtained from 16 multiple myeloma (MM) patients and observed that serum LPA level was significantly higher in MM patients (5.3 +/- 0.5 nmol/mL) than in normal controls (1.7 +/- 0.3 nmol/mL). LPC level was also higher than that in normal controls, and it correlated significantly with the concentration of LPA (r = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 20 publications
6
68
0
1
Order By: Relevance
“…S1P also inhibits adenylyl cyclase, ERK1 activation (Lee et al, 1996), tumor cell invasion (Sadahira et al, 1992), and apoptosis (Radeff-Huang et al, 2004). LPA is secreted by ovarian cancer cells (Fang et al, 2002;Tanyi et al, 2003), prostate cancer cells (Xie et al, 2002), multiple myeloma (Sasagawa et al, 1999), and many other cancer cell types. In fact, it was suggested that LPA is a marker for ovarian cancer patients since it is highly increased in the serum and ascitic fluids of women with this disease (Xu et al, 1998), with the level in these patients capable of reaching up to 500 M. Furthermore, LPA induces the release of angiogenic factors such as vascular endothelial growth factor (Hu et al, 2001) and is involved in neovascularization and tumor growth and survival.…”
Section: A Lysophospholipidsmentioning
confidence: 99%
“…S1P also inhibits adenylyl cyclase, ERK1 activation (Lee et al, 1996), tumor cell invasion (Sadahira et al, 1992), and apoptosis (Radeff-Huang et al, 2004). LPA is secreted by ovarian cancer cells (Fang et al, 2002;Tanyi et al, 2003), prostate cancer cells (Xie et al, 2002), multiple myeloma (Sasagawa et al, 1999), and many other cancer cell types. In fact, it was suggested that LPA is a marker for ovarian cancer patients since it is highly increased in the serum and ascitic fluids of women with this disease (Xu et al, 1998), with the level in these patients capable of reaching up to 500 M. Furthermore, LPA induces the release of angiogenic factors such as vascular endothelial growth factor (Hu et al, 2001) and is involved in neovascularization and tumor growth and survival.…”
Section: A Lysophospholipidsmentioning
confidence: 99%
“…In a colon cancer cell line, LPA increases the synthesis of macrophage migration inhibitory factor, which promotes tumor growth (26). LPA levels are elevated in the blood of patients with multiple myeloma (27).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that LPA is secreted in large quantities by several tumor cells, such as ovarian, prostate and multiple myeloma, among others [9][10][11], it can be speculated that LPA may recruit NK cells into the sites of tumors, where NK cells secrete cytokines such as IFN-+ that may provide a suitable environment for the growth of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a comprehensive study, Zhou et al [6] observed that LPA and PA induce the chemotaxis, haptotaxis and calcium mobilization in human monocytes. LPA is not chemoattractant for breast cancer cells [7], but is secreted by ovarian cancer cells [8,9], prostate cancer cells [10], multiple myeloma [11], and many other cancer cell types [9]. Consequently, LPA was suggested to be a potential marker for various gynecological cancers [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation